Survey of the Use of Information Communication Technology Tools in CIMB Bank for Decision Making - Alfakhri, Mohamed Youniss Youssif (2010)
Nowadays, most people use the internet and other forms of information and communication technology to do their business for the purpose of better services. Also people are looking for services that can be not only affordable but also accessible anywhere anytime. Many business organizations are using ICT in various purposes, mainly being performing their activities effectively. The main objective of the study is to investigate the use of ICT tools in business organizations for decision making. The study aims to perform a survey in order to determine the extent of the use of ICT as well as factors associated with the applications among private business offices operations within CIMB Bank, Kedah.